Rent building, rent sharing: A panel country-industry empirical analysis - Philippe Askenazy; Gilbert Cette; Paul Maarek (Institute for the Study of Labor (IZA), 2012)
Through panel estimates using OECD country-industry statistics, this paper aims to clarify the determinants of rent creation and the mechanisms of rent sharing, and the role of market regulations in these processes. The empirical analysis is carried out in two steps. The first explains the rent creation process. For each country-industry-year observation, the size of rents, measured by the value added price relative to the GDP price, is assumed to depend solely on direct anti-competitive regulations on services and goods. The second step explains the rent sharing process. Three destinations of rents are distinguished for each country-industry-year observation: upstream industries, capital and labour. The main empirical findings are as follows. Regarding the rent creation, direct anti-competitive regulations are associated with a very significant rise in rent size. Concerning the rent sharing, the capital share in value added appears to i) increase with rent size, decrease with anti-competitive regulation in upstream sectors and increase with the industry specific output gap; ii) decrease with the national output gap, increase with the national employment rate and decrease with employment protection regulation; iii) increase with the interaction of rent size and the unemployment rate and decrease with the interaction of rent size and employment protection regulations. These results confirm the existence of three destinations for rents. They also show that the magnitude of each destination depends on the market power of its beneficiary. All these results are robust to a variety of sensitivity checks.
urn:nbn:de:101:1-201207126998
Keywords: E25; J20; J30; 330; rents; capital share; prices; market regulations; output gap; unemployment; Rententheorie; Gewinnquote; Branche; Marktmechanismus; Regulierung; Gesamtwirtschaftliche Produktion; Arbeitslosigkeit; Großbritannien